ANALISIS BAHASA PRAGMATIK ADEGAN MENAKJINGGA GANDRUNG DALAM LANGENDRIYAN RANGGALAWE GUGUR - Maryono Maryono (Greget, 2013)
This paper aims to discover the meaning of the Menakjingga Gandrung scene inLangendriyan Ranggalawe Gugur through a study of the pragmatic language used. The researchuses a descriptive qualitative methodology. The theoretical basis used for analyzing the object ofthe study is a combination of pragmatic theories and performing arts theories. The target of thepragmatic theories is the types of linguistic texts while the performing arts theories are directedtowards physical elements of a non-linguistic nature.Based on a study of the verbal and non-verbal components in the Menakjingga Gandrungscene in Langendriyan Ranggalawe Gugur, it is evident that its theme is that of gandrungan orunrequited love. The story portrays the love of Adipati Menakjingga for Queen AyuKencanawungu. His love remains unrequited despite his power and supernatural abilities. Thereality of this situation is also contained in the words of the song Asmarandana which statesâ€œgegaranÃ© wong akrami dudu bandha dudu rupa among ati pawitanÃ©â€ (the main asset for aperson to love is not wealth, nor is it good looks, but rather comes from the heart). Therefore, a loveaffair is truly determined by the compatibility and harmony between two peopleâ€™s hearts whenthey are sincere in sharing their love for one another.Â